Stan i perspektywy rozwoju bankowości elektronicznej w Polsce - Leszczyńska, Maja (The current state and perspectives of development of e-banking in Poland, 2005)
Electronic banking is a term for the process by which a customer may perform banking transactions electronically without visiting any kind of institution. This paper presents peculiarities of different kind of e-banking (point of sales, home/office banking, TV banking, phone banking, SMS banking, WAP banking and Internet banking). In order to meet the expectations of customers many Polish banks started to offer this kind of services and nowadays we can observe their rapid growth the in Poland. The article presents the current state of e-banking in our country. The direction and perspectives of development in this area will be also presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (8); 2005; nr 1094, s. 224-234